Frontiers of Photography : Life Library of Photography. (New York : Time-Life Books, 1972)
Contents : Clues to the Future ; Cameras in the Computer Age ; Photography's Changing Images ; Mixing the Media ; Into the Third Dimension ; A New Wave of Abstraction
Engels
boek